The use of rubber tire chips as biofilm carrier in horizontal subsurface flow constructed wetland - Senoro, Delia B. (March 2009)
This research study presents the potential use of scrap rubber tire chips as biofilm carrier in horizontal subsurface flow constructed wetland. Diminishing water supply in an increasing freshwater demand; increasing scrap rubber tires limited appropriate final destination are current situations of developing countries such as the Philippines. These conditions without proper immediate mitigation will lead to insanitation that eventually degrade the environment and cause loss of lives. Therefore, study that could aid in giving solution to lack of water resource and bulky solid waste management is important. Two parallel tanks as constructed wetland systems composed of free water surface (FWS) and subsurface flow (SSSF) were installed and designated as A and B. SSF. A containing gravel whereas SSF B contained rubber tire chips and gravel. FWS tanks were planted with Typha Orientalis Presl. while SSF tanks with Phragmites Communis L. Both systems were subjected to the same conditions such that only differences caused by the type of biofilm carrier were monitored and recorded. FWSs were installed for primary treatment since SSFs are favorable to secondary wastewater. Focus of the study was given to SSF systems as the primary objective was to determine whether rubber tire chips could be a potential biofilm carrier in subsurface flow constructed wetlands. Hydraulic characteristics were investigated; water quality, porosity and plant density were monitored regularly. Sampling points were at the inlet of the system, outlets of FWS, which then became the inlet for SSF, and the outfull from SSF. Experimental methods for the water quality monitoring were carried out based from the Standard Methods for the Examination of Water and Wastewater by APHA whereas empirical modeling was used for the determination of hydraulic properties, biofilm specific surface area and growth rates. Rhodamine WT and Spectroflourometer were used to quantify the actual detention time of pollutants and to determine the type of flow and mixing patterns of the systems. Monod Kinetics Model was specifically used for the quantification of biofilm specific growth rates. Results below are presented in order, data from SSF A comes first followed by SSF B. These are as follows: (1) pH range was circumneutral for both systems, (2) water temperature for both systems ranged from 12-33 ̊C; mean water temperature was almost equal to the mean of air temperature during autumn; (3) DO is SSF A was higher than in SSF B; (4) SSF containing RTC possessed excellent hydraulic properties by having tm as 98% of theoretical detention time (tn) and mixing pattern of continuously stirred tank reactor, CVSTR, model; (5) COD mean removals during 132 days were 35.93 and 19.13%; howver, SSF B recorded the maximum COD removal of 93.40% at water temperature of 23 ̊C; (6) NH3-N mean removals were 32.42 and 30.31% and the maximum removals were 91.43 and 78.37%; (7) the mean COD concentration of SSF A was greater than three times that of its mean BOD concentration while in SSF B the mean COD concentration was greater than twice its mean BOD concentration. (8) the mean total phosphorus, TP, removals ere 15.48 and 48.41% and the maximum recorded TP removals were 59.77 and 95.27%; (9) the total Fe leaching potential was 235.03 mg 1-1 d-1 for every m3 of rubber tire chips; (10) nitrifying bacteria were efficient in SSF A at water temperature greater than 25 ̊C whereas denitrifying bacteria were efficient in SSF B at water temperature gretaer than 25 ̊C; (11) overall biofilm growth rates in SSF B were almost 5 times greater SSF A. Based on the above mentioned results, it was concluded that rubber tire chips is a surface favorable to oxidation and microbial growth, hence, potential biofilm carrier for HSSF application favorable to Philippines setting. Utilization of rubber tire chips as biofilm carrier in horizontal subsurface flow constructed wetlands offers mitigation to wastewater management and disposal problem. Results of this study provide solutions to bulky waste management and lack of water resource by providing fresh water for commercial, agriculture, industrial and domestic uses.
Thesis (Ph.D. Environmental Engineering)--University of the Philippines Diliman.
Keywords: Crumb rubber; Biofilms; Constructed wetlands; Sewage -- Purification